Sex and Literacy in Roman Spain - Díaz Ariño, Borja (Gerión. Revista de Historia Antigua, 2023)
This paper analyses around 20 graffiti on walls and pottery which come from Spain and are datable between the first and third centuries CE, which contain erotic text. These documents offer interesting information on the sexual customs of the population of Roman Spain, but also allow reflection on the spread of literacy among its most popular sectors.